Pengembangan Instrumen Asesmen Kompetensi Minimum Literasi Membaca dan Numerasi Berbasis STEM pada Topik Stoikiometri - Windi Putri Jayanti; Nahadi; Wiwi Siswaningsih (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to develop and validate a STEM-based stoichiometry assessment instrument aligned with the Minimum Competency Assessment (AKM) framework to measure students’ reading literacy and numeracy skills. STEM aspects were integrated into the items through science, technology, engineering, and mathematics contexts embedded in stoichiometry problems. The study employed a development and validation research method. Initially, 50 items were developed, and content validation results showed that 48 items met the validity criteria with a Content Validity Ratio (CVR) value of 1.00. From the validated items, 30 items were selected for empirical testing, consisting of 16 numeracy items and 14 reading literacy items distributed across 11 reading texts. The empirical testing results indicated that 23 out of 30 items were valid and reliable. Most items were categorized as having a moderate difficulty level and acceptable discriminative power. Furthermore, students’ reading literacy and numeracy competencies were categorized as basic. Therefore, the developed instrument is feasible as an alternative assessment tool to support AKM-oriented chemistry learning and evaluation.